2019
DOI: 10.1063/1.5065477
|View full text |Cite
|
Sign up to set email alerts
|

State-of-health estimation for lithium battery in electric vehicles based on improved unscented particle filter

Abstract: This paper proposes an effective method to estimate the state of health (SOH) of a lithium-ion battery based on the ohm internal resistance R0. Unlike other estimation methods, this work considers the variation of R0 with the state of charge (SOC). The improved unscented particle filter (IUPF) is presented to track and predict R0. That is, an unscented Kalman filter (UKF) is used to generate an importance probability density function in the particle filter, and a method to select the fittest particle in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Tracking these aging characteristics, they estimated SOH and RUL with a high accuracy compared to an artificial neural network-based model. Likewise, references [67,68] developed a promising modified PF algorithm that avoids particle degradation. For example, Shi et al [68] demonstrated that improved unscented PF (IUPF) had better accuracy than unscented Kalman filter (UKF) and unscented particle filter (UPF) model prediction of ohmic internal resistance (R o ) and SOH.…”
Section: Gray-box Methods Are Hybrid Prognostics Between White and Blmentioning
confidence: 99%
“…Tracking these aging characteristics, they estimated SOH and RUL with a high accuracy compared to an artificial neural network-based model. Likewise, references [67,68] developed a promising modified PF algorithm that avoids particle degradation. For example, Shi et al [68] demonstrated that improved unscented PF (IUPF) had better accuracy than unscented Kalman filter (UKF) and unscented particle filter (UPF) model prediction of ohmic internal resistance (R o ) and SOH.…”
Section: Gray-box Methods Are Hybrid Prognostics Between White and Blmentioning
confidence: 99%
“…Tracking these aging characteristics, they estimated SOH and RUL with a high accuracy compared to an artificial neural network-based model. Likewise, references [67,68] developed a promising modified PF algorithm that avoids particle degradation. For example, Shi et al [68] demonstrated that improved unscented PF (IUPF) had better accuracy than unscented Kalman filter (UKF) and unscented particle filter (UPF) model prediction of ohmic internal resistance (R o ) and SOH.…”
Section: Gray-box Methodsmentioning
confidence: 99%
“…Copper, silver, gold, carbon, aluminum, nickel, indium tin oxide, tin, graphene, graphene oxide, PEDOT:PSS, polyaniline, iron, graphite [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Semiconductors Zinc oxide, silicon, zinc selenide, indium-gallium-zinc oxide, cadmium selenide, gallium arsenide, MALH [59][60][61][62][63][64] Resistors Aluminum oxide, hafnium dioxide, poly(4-vinylphenol), spin-on glass, parylene, solid electrolytes [65][66][67][68][69][70][71][72] Table 3.…”
Section: Conductorsmentioning
confidence: 99%
“…Wassiliadis, N et al [14] proposed an approach tackling battery SOH estimation, which consists of two extended Kalman filters (EKFs), that synchronously estimate both the battery SOH and model parameters. Shi, E et al [15] proposed a method that uses improved unscented particle filter (IUPF) to estimate the ohm internal resistance, and then estimates the SOH based on the internal resistance. The testing results show that IUPF has certain advantages, with the SOH estimation error always less than 3%.…”
Section: Review Of Estimation Approachesmentioning
confidence: 99%